Pendampingan Implementasi Projek Penguatan Profil Pancasila pada Anak Usia Dini Di Kecamatan Abiansemal - Suryaningsih, Ni Made Ayu; Cahaya, I Made Elia; Endah Poerwati, Christiani (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
Widya Sari Kindergarten and Widya Kumara Kindergarten are early childhood education institutions or PAUD under the Swadarma Karya Foundation, Darmasaba Village, Abiansemal. The two institutions have played an important role in the advancement of early childhood education in Darmasaba village since 1975 until now. In facing the challenges of future developments, the two institutions always try to keep abreast of the changes that occur, especially related to the development of science and technology, including the implementation of the new "Freedom to Learn" curriculum. Implementation of the Project to Strengthen the Pancasila Student Profile in PAUD units is an integral part of the Merdeka Curriculum. The two partners have a strong will to pursue and implement this P5, but do not yet have an overview of its implementation. The method used in this assistance is through workshops providing material and training in the implementation of project activities to strengthen the Pancasila profile. at the end of the activity, it can be concluded that there was an increase in the partner's ability to implement project activities to strengthen the Pancasila profile, after participating in mentoring activities.